Inhibitory Control, Task/Rule Switching, and Cognitive Planning in Vascular Dementia: Are There Any Differences From Vascular Aging? - Pantsiou, Krystallia; Sfakianaki, Ourania; Papaliagkas, Vasileios; Savvoulidou, Dimitra; Costa, Vassiliki; Papantoniou, Georgia; Moraitou, Despina (Frontiers in Aging Neuroscience, 2018)
Recent studies have shown that older adults diagnosed with Vascular Dementia (VaD) exhibit cognitive deficits related with executive functions. In addition, according to “vascular hypothesis of cognitive aging”, community-dwelling older adults having risk factors for vascular disease development may suffer from cognitive decline of the same type. The present study aimed at developing a small and reliable diagnostic tool for VaD, which will measure specific executive functions. In particular, the study sampleconsisted a total of 60 adults divided into three groups: a) healthy young adult controls; b) community-dwelling older adults which are at risk of developing vascular disease (RVD); c) older adults with a diagnosis of VaD. We examined three types of executive functions: inhibition, switching, and planning. The results showed that planning and cognitive flexibility as combination of inhibition and switching are greatly affected by VaD. Hence, tasks examining planning and cognitive flexibility seem to be very useful to differentiate VaD from vascular aging experienced by community dwelling older adults. Moreover, specific indices for VaD diagnosis are proposed on the basis of the findings.